Cost-utility analysis of LEGO based therapy for school children and young people with autism spectrum disorder: results from a randomised controlled trial. Issue 1 (17th January 2022) - Wang, Han-I; Wright, Barry Debenham; Bursnall, Matthew; Cooper, Cindy; Kingsley, Ellen; Le Couteur, Ann; Teare, Dawn; Biggs, Katie; McKendrick, Kirsty; de la Cuesta, Gina Gomez; Chater, Tim; Barr, Amy; et al.
Abstract : Objectives: To assess the cost-effectiveness of LEGO-based therapy compared with usual support. Design: Cost-utility analysis alongside randomised control trial. Setting: Mainstream primary and secondary schools in the UK. Participants: 248 children and young people (CYP) with autism spectrum disorder (ASD) aged 7–15 years. Intervention: LEGO-based therapy is a group social skills intervention designed specifically for CYP with ASD. Through play, CYP learn to use the skills such as joint attention, sharing, communication and group problem-solving. CYP randomised to the intervention arm received 12 weekly sessions of LEGO-based therapy and usual support, while CYP allocated to control arm received usual support only. Main outcome measures: Average costs based on National Health Service (NHS) and personal social services perspective and quality-adjusted life years (QALYs) measured by EQ-5D-Y over time horizon of 1 year were collected during the trial. Incremental cost-effectiveness ratio (ICER) was calculated, and non-parametric bootstrapping was conducted. The uncertainty around the ICER estimates was presented using cost-effectiveness acceptability curve (CEAC). A set of sensitivity analyses were conducted to assess the robustness of the primary findings. Results: After adjustment and bootstrapping, on average, CYP in LEGO-based therapy group incurred less costs (incremental cost was −£251 (95% CI −£752 to £268)) and gained marginal improvement in QALYs (QALYs gained 0.009 (95% CI −0.008 to 0.028)). The CEAC shows that the probability of LEGO-based therapy being cost-effective was 94% at the willingness-to-pay threshold of £20 000 per QALY gained. Results of sensitivity analyses were consistent with the primary outcomes. Conclusion: Compared with usual support, LEGO-based therapy produced marginal reduction in costs and improvement in QALYs. Results from both primary and sensitivity analyses suggested that LEGO-based therapy was likely to be cost-effective. Trial registration number: ISRCTN64852382 .